Neutral lipid storage disease with myopathy: A 10-year follow-up case report - Sara Missaglia; Daniela Tavian; Corrado Angelini (PAGEPress Publications, 2022)
Mutations in PNPLA2 gene encoding for adipose triglyceride lipase (ATGL), involved in triglyceride degradation, lead to an inborn error of neutral lipid metabolism. The disorder that results in abnormal storage of neutral lipid is known as neutral lipid storage disease with myopathy (NLSDM). We report the follow-up of a 30-year-old woman with NLSDM, asymptomatic until age 23. At the age of 18, a high level of CPK and neutral lipid abnormal accumulation in muscle and skin cells suggested NLSDM diagnosis, afterwards confirmed by PNPLA2 analysis. After 5 years, she developed weakness in the upper and lower extremities. She was put on a low-fat diet with medium-chain triglycerides (MCT) oil supplementation but, although her CPK level decreased, myopathy continued to progress. At present, she presents severe skeletal myopathy without cardiac involvement. In this patient, no beneficial effects on progressive skeletal muscle weakness were detected after the MCT diet, probably due to complete loss of PNPLA2 expression.